Negosiasi Pertanian dan Pariwisata Serta Pendapatan Petani di Daya Tarik Wisata Ceking Terrace - LAKSMI, ANAK AGUNG ISTRI MAS SURYA; PITANA, I GDE; SUAMBA, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Negotiation of Agriculture and Tourism and Farmers’ Income in Ceking Terrace Tourist Attraction Ceking Terrace Tourist Attraction is one of the tourist attractions that has natural beauty with Terraces as the main attraction, located in Kedisan Village, Tegallalang District, Gianyar Regency, Bali. The tourist attraction is managed by Tegallalang Pakraman Village. This study aims to analyze the negotiation process between the management of Ceking Terrace Tourist Attraction (BPOWC) and farmers in utilizing Ceking Terrace Tourist Attraction as a sustainable tourist attraction and to analyze farmers' income. The result suggests that the negotiation has not been well resolved. Farmers demanded a negotiation at the end of the land lease contract to get 50% of the tourism revenue, however the management would not comply with the request of the farmers. The farmers’ overall household income from on farm is only 5.51%, whereas from non-farm (non-agriculture) is 94.49%. The biggest non-farm income comes from tourism retribution per year of 86.81%. This shows that all respondents have an additional source of income from tourism retribution that can be used as a support to fulfill their daily needs and farmers depend on tourism activities. It is recommended that farmers further develop the agricultural sector such as making agricultural innovations and products. The management should consider to increase ticket prices and to make pre-wedding photo packages for tourists. The management should also consider to add the farmers group into their organization structure in order to keep all the outgoing and ingoing cost transparency and to minimize conflict.